A purposive approach to labour law - Davidov, Guy, 1970- (Oxford : Oxford University Press, 2016)
This volume explores the societal goals behind labour laws - through an analysis of normative justifications and critiques - and examines what actions are needed to better advance these goals, by way of purposive interpretation and legal reform.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 9, 2016).
Keywords: Labor laws and legislation; Labor laws and legislation -- Interpretation and construction; Law